Entrando na partida: a formulação de políticas de comunicação e cultura para jogos digitais no Brasil entre 2003 e 2014 - Zambon, Pedro Santoro [UNESP] (2015)
This research aims to describe how was the process for the formulation of public policies concerning the communication and culture for the digital games in Brazil, along the first twelve (12) years of PT (Workers Party) government. The trajectory of games as an object of public policies has been established - starting from their origin of those policies in software related ones, including their treatment a cultural policy, to finally include them in the category of communication policy content. The political processes that supported such transition from a systemic agenda for the government has been identified, followed by a process of mapping and systematization of laws, projects, tenders, comissions and government programs, in a federal level. Starding from the policies cycle, it has been observed the formulation stage - which includes the decision-making process - under the perspective of the incrementalist model, from Lindblom (1959). Understanding the adjustment of interests centrally, the role of both state actors and stakeholding groups in the formulation, the decision-making arenas has been seen as a way to identify them. Complementing those processes with interpretations of interviews that sometimes reveal information which is not presented in official documents and media, policies formulated by the government actors were characterized according to the typology of Wilson (1983), identifying costs and benefits among different sectors in the string value of digital games. The application of this typology has enabled us to realize that in addition to initiatives being that have been developed incrementally, based on devices and policies of other sectors, stakeholding groups have demonstrated an active role in decision making, and the chain industry most benefited in the development cycle